Variations in Alaska tidewater glacier frontal ablation, 1985–2013. Issue 1 (26th January 2015) - McNabb, R. W.; Hock, R.; Huss, M.
Abstract Our incomplete knowledge of the proportion of mass loss due to frontal ablation (the sum of ice loss through calving and submarine melt) from tidewater glaciers outside of the Greenland and Antarctic ice sheets has been cited as a major hindrance to accurate predictions of global sea level rise. We present a 28 year record (1985–2013) of frontal ablation for 27 Alaska tidewater glaciers (representing 96% of the total tidewater glacier area in the region), calculated from satellite‐derived ice velocities and modeled estimates of glacier ice thickness. We account for cross‐sectional ice thickness variation, long‐term thickness changes, mass lost between an upstream fluxgate and the terminus, and mass change due to changes in terminus position. The total mean rate of frontal ablation for these 27 glaciers over the period 1985–2013 is 15.11 ± 3.63Gta−1. Two glaciers, Hubbard and Columbia, account for approximately 50% of these losses. The regional total ablation has decreased at a rate of 0.14Gta−1 over this time period, likely due to the slowing and thinning of many of the glaciers in the study area. Frontal ablation constitutes only ∼4% of the total annual regional ablation, but roughly 20% of net mass loss. Comparing several commonly used approximations in the calculation of frontal ablation, we find that neglecting cross‐sectional thickness variations severely underestimates frontal ablation.